Looking beyond Meaning in the Advanced Ndebele Dictionary - Khumalo, Langa (Lexikos, 2009)
Abstract: It is an established view in lexicography that the most important function of early dictionaries was to provide information on the meaning of words of a particular language. Over the years, tendencies have emerged with modern dictionaries providing detailed linguistic information resulting in more informa-tive dictionaries. This article discusses the presentation of grammatical information, pronunciation, tone marking and usage labels and the structure and content of the back matter in the prospective Advanced Nde-bele Dictionary (henceforth AND), which will be a successor to Isichazamazwi SesiNdebele (2001), the first-ever monolingual dictionary in Ndebele.1 It is therefore the inclusion of this additional information that is exam-ined in this article. The AND is still restricted to the planning stages. The work that has been done on the dictionary has been confined to academic articles about the dictionary’s structure and content. The current article is a third instalment on the AND following on Khumalo 2003 and 2007.